Pengaturan Tentang Warisan dengan Akta Hibah Wasiat Berdasarkan Sistem Hukum Waris di Indonesia - I Nyoman Oky Krisnanda; I Nyoman Putu Budiartha; I.B. Gede Agustya Mahaputra (Jurnal Interpretasi Hukum, 2022)
In addition to the inheritance system drawn from the lineage, the community can also appoint heirs outside the lineage. This can be done by making a will. The implementation of the contents of the will grant deed is sometimes a problem, especially for indigenous people who apply customary law. The purpose of the study was to determine the process of making will grants and the implementation of wills based on the Civil Code, to find out the legal consequences of implementing testamentary grants made with a testamental grant deed by indigenous groups whose inheritance system uses customary law. The type of normative legal research with a legal and conceptual approach. The results showed that the implementation of a will can be carried out through a notary by making a Certificate of Inheritance by a notary after checking whether or not the last will is on the list of will centers. For a will in the form of land rights, the Inheritance Rights Certificate is registered at the Office of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency to carry out changes to the data in the land certificate referred to in the will. A will grant deed made by indigenous people (Balinese people) who apply customary inheritance law does not become invalid, because the will grant deed is part of western civil law and its manufacture is subject to the Civil Code or because the person who makes the will is subject to customary law.